1969
DOI: 10.1111/j.1476-5381.1969.tb07988.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tremor and change in brain acetylcholine concentration produced by injection of tremorine or oxotremorine in the rat

Abstract: The relationship between tremor and change in brain acetylcholine concentration after the injection of tremorine or oxotremorine has been investigated in rats. Tremorine produced a significant increase in whole brain acetylcholine and in tremor 5 min after injection. After this time tremor subsided but brain acetylcholine continued to increase. Oxotremorine produced tremor within 30 sec. This became maximal within 5 min of injection and then declined rapidly. The brain acetylcholine concentration showed a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Quantitative estimation of tremor Tremor was determined by a method described previously (Cox & Potkonjak, 1969b) in which a rat is placed in a Perspex box attached to a gramophone pick-up head and the output produced by the pick-up in response to movements of the rat is connected to a wide band preamplifier (7P3A) of a Grass Polygraph (Model 7) and to a polygraph integrator (7P1OA) to give an integrated value of the tremor recording. Since the oxotremorine tremor in the rat is almost immediate in onset and reaches a maximum in the first 5 min after injection (Cox & Potkonjak, 1969b) tremor was recorded for a 5 min period beginning 30 s after oxotremorine injection. One complete deflection of the integrator pen was given an arbitrary value of 100 tremor units.…”
Section: Brain Acetylcholine Estimationmentioning
confidence: 99%
“…Quantitative estimation of tremor Tremor was determined by a method described previously (Cox & Potkonjak, 1969b) in which a rat is placed in a Perspex box attached to a gramophone pick-up head and the output produced by the pick-up in response to movements of the rat is connected to a wide band preamplifier (7P3A) of a Grass Polygraph (Model 7) and to a polygraph integrator (7P1OA) to give an integrated value of the tremor recording. Since the oxotremorine tremor in the rat is almost immediate in onset and reaches a maximum in the first 5 min after injection (Cox & Potkonjak, 1969b) tremor was recorded for a 5 min period beginning 30 s after oxotremorine injection. One complete deflection of the integrator pen was given an arbitrary value of 100 tremor units.…”
Section: Brain Acetylcholine Estimationmentioning
confidence: 99%
“…It could exert its effects by causing a release of acetylcholine from endogenous stores. Cox & Potkonjak (1969) found that oxotremorine does, in fact, cause an increase in brain acetylcholine in rats but there is a 15 min time lag between dosing and the observed rise in acetylcholine. As the hypertensive response to oxotremorine is almost immediate, it does not therefore seem likely that this effect is due to the latter mechanism of action, although it is possible that acetylcholine could be redistributed, thus increasing its availability at muscarinic receptors, with no immediate change in total brain content.…”
Section: Effect Of Vagotomymentioning
confidence: 99%
“…This drug has marked parasympathomimetic actions, blockade of which can be used to measure the peripheral anticholinergic potency of atropine-like drugs. In addition it produces muscular tremors in a variety of species of animals, and although there has been much discussion as to its mode of action in producing these tremors there is now evidence (Bebbington & Brimblecombe, 1965;Cox & Potkonjak, 1969a, b) to suggest that it is due to an interaction with central acetylcholine receptors analogous to peripheral muscarinic receptors. Thus, blockade of oxotremorine-induced tremors can be used to give a measure of central anticholinergic potency.…”
Section: Introductionmentioning
confidence: 99%